Answer:
The option 1) i.e. (2, -6) is true.
Step-by-step explanation:
Considering the function
[tex]f(x) = 3x^{2} - 12x + 6[/tex]
[tex]\mathrm{Write}\:3x^2-12x+6\:\mathrm{in\:the\:form:\:\:}x^2+2ax+a^2[/tex]
= [tex]3x^{2} -12x+6[/tex]
[tex]\mathrm{Factor\:out\:}3[/tex]
= [tex]3(x^{2} -4x)+6[/tex]
Completing the square:
[tex]=3\left(x^2-4x+2+\left(-2\right)^2-\left(-2\right)^2\right)[/tex]
As
[tex]x^2+2ax+a^2=\left(x+a\right)^2[/tex]
[tex]x^2-4x+\left(-2\right)^2=\left(x-2\right)^2[/tex]
[tex]\mathrm{Complete\:the\:square}[/tex]
[tex]=3\left(\left(x-2\right)^2+2-\left(-2\right)^2\right)[/tex]
[tex]=3\left(x-2\right)^2-6[/tex]
The vertex form of a quadratic function [tex]f(x) = a(x-h)^{2} + k[/tex], where (h, k) be the vertex of the parabola.
The vertex form of the equation is: [tex]f(x)=3\left(x-2\right)^2-6[/tex]
If we may compare this equation with the general vertex form, we will find that h = 2 and k = -6, so the vertex is at (2, -6).
Therefore, option 1) i.e. (2, -6) is true.
Keywords: completing the square, function
Learn more about completing the square from brainly.com/question/12752635
#learnwithBrainly